Bizarre things we've eaten - Leavitt, Amie Jane (North Mankato, Minnesota Capstone Press, 2016)
"Introduces readers to some of the more bizarre foods humans have eaten throughout history"-
A gift from book Africa
Customs & folklore
1 2 11 13
Keywords: Food preferences -- Juvenile literature; Food habits -- History -- Juvenile literature